Their fractured light : a Starbound novel - Kaufman, Amie; Spooner, Meagan (Hyperion, 2015)
When a foiled attempt to infiltrate the corrupt LaRoux Industries forces hacker Gideon Marchant and revenge-seeking Sofia Quinn into a fragile alliance, they join forces with Icarus survivors Tarver and Lilac and Avon's protectors Flynn and Jubilee, to take down the most powerful corporation in the galaxy--before LRI's secrets destroy them all.